Aplicação de design estratégico no pólo joalheiro de Guaporé - Cruz, Karen Rejane Viana Abs da (Universidade do Vale do Rio dos Sinos, 2010)
The current study is dedicated to the research into the expanding value of the cities in relation to its emerging industries in the age of globalization.With the expansion of connections and telecomunication, many places suffer from what we call “deterritorialisation”, where the economic growth is said places, move from one central point and expands further than the physical limits of where it once originated. Due to this factor, the invention of a strategic, regional design plan is proposed with the aim to attract interest and wealth once again to the specified areas, showing thier potential, whilst also respecting the historic and culture values of each place. The aim of the research is diagnose the gaps and potential existing in the area/region. To offer strategic direction for the elaboration of future projects and areas in search of a growth in trade. The method applied in the study in this case is of strategic design which takes into account product system in their physical aspects, quality of service, overall experience and the general aspects of communication. When strategic design is applied in the area we call it territorial design. This case study has as its heading – Guaporé – The pivital point of the jewellery industry in the state of Rio Grande do Sul. Guaporé is home to a great number of small businesses, of which, the majority are dedicated to the production of Gold and Silver plated jewellery. The point in question presented is raised in the following question “ How can the region of Guapore be valued based on its jewellery industry? ”. This research proposed is as a direct fundamental the following factors. The formation of an interorganizational cooperative to help expand and promote Guaporé as an important centre in the market. The proposal to promote, the cities potencial due to its regional identity with design, joint innovation teamed with local traditional customs. Encouraging the growth of an important design source; the making of brands, a strive for quality, thorough communication, intergrated action planning and interactivity between all of the small businesses, the local community and its politics.
Keywords: Design estratégico; Design territorial; APL’s; Redes de cooperação interorganizacional; Strategic design; Territorial design; Networks interorganisational cooperative; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial